Biodegradation of polycyclic aromatic hydrocarbons by soil fungi - Clemente,Andrea R. (2001)
Thirteen deuteromycete ligninolytic fungal strains were grown in media containing polycyclic aromatic hydrocarbons (PAHs), for 6 and 10 days. The PAHs were added directly with the inocula or on the third day of cultivation. A selection of the best strains was carried out based on the levels of degradation of the PAHs and also on the ligninolytic activities produced by the fungi. The selected strains were cultivated for 3, 6, 9, 12 and 15 days in the PAHs-containing media. Degradation of PAHs, as measured by reversed-phase HPLC on a C18 column, varied with each strain as did the ligninolytic enzymes present in the culture supernatants. Highest degradation of naphthalene (69%) was produced by the strain 984, having Mn-peroxidase activity, followed by strain 870 (17%) showing lignin peroxidase and laccase activities. The greatest degradation of phenanthrene (12%) was observed with strain 870 containing Mn-peroxidase and laccase activities. When anthracene was used, the strain 710 produced a good level of degradation (65%).